Green Human Resource Management Practices and Initiatives on Organizational Performance: A Review Perspective - Kandel, Sudarshan; Thapa, Kiran; Paudel, Prabhat (Kalika Journal of Multidisciplinary Research, 2024)
This article aims to investigate and assess the activities and procedures associated with Green Human Resource Management (Green HRM) within the context of a corporate framework. This review research aims to develop a complete analytical and theoretical framework for the literature on green human resource management (GHRM). The literature presents concise notions concerning green dimensions, features, and theories. These concepts integrate environmental management principles with human resources practices in order to improve both the performance of the organization and its sustainability. The evaluation investigates the impact of fundamental green practices on environmental performance and overall company success. These Green dimensional activities include green recruiting, selection, training, incentive and compensation, performance management, employee participation, health and safety, and more. The study suggests further research and practical research seeking to incorporate sustainability into their HR strategies.